Addressing disparities: unmet health needs and its impact on health-related quality of life - Yetim, Birol; Ugurluoglu, Ozgur (Routledge Journals, Taylor & Francis Ltd, 2025)
This study focuses on unmet health needs in T & uuml;rkiye and their effects on health-related quality of life. It also aims to examine how cardiovascular diseases influence individuals' quality of life. To achieve these objectives, data from the T & uuml;rkiye Health Surveys, conducted by Turkish Statistical Institute, were analyzed. The study sample of individuals aged 18 and over. After excluding incomplete responses, a total of 70 000 observations were included in the analysis. To assess the quality of life, 15 questions from the surveys were selected based on their compatibility with the EQ-5D-3 L scale. The validity and reliability of these items were tested through factor analysis. Descriptive statistics, t-tests and regression models were used to analyze the data. The findings revealed that unmet health needs significantly reduce health-related quality of life. Individuals who could not access healthcare services due to financial difficulties, transportation issues or long waiting times reported lower quality of life scores. Furthermore, women, individuals with lower educational attainment and income levels and those diagnosed with cardiovascular diseases were found to have significantly lower quality of life. The study concludes that unmet health needs remain a critical health concern in T & uuml;rkiye, especially among disadvantaged and chronically ill populations. It is recommended that policymakers prioritize strategies to reduce financial and systemic barriers in healthcare access. Increasing educational and economic opportunities and enhancing support for patients with chronic diseases could contribute to improving overall health outcomes. Addressing these disparities will help align the healthcare system with the evolving needs of the population and promote a more equitable approach to health service delivery.
Keywords: Cardiovascular diseases; EQ-5D-3L; health-related quality-of-life; unmet health needs